The Effect of Giving Dragon Fruit Skin Extract (Hylocereus costarisensis) on the Quality of Se'i Beef Meat - R. S. Sembong; G. E. M. Malelak; P. R. Kale (Jurnal Sain Peternakan Indonesia, 2022)
This research has been conducted to determine the quality of processed meat mixed with dragon fruit skin extract (Hylocereus costarisensis) and determine the length of time of different watering. The method used was an experimental method with a design using a complete randomized design (CRD) consisting of 2 4x3 pattern factors consisting of 4 factors of dragon skin extract level of 0% (control), 40%, 60%, 80%, and 3 factors of duration time of watering 6 hours, 12 hours, 18 hours. Combining these two factors produces 12 combinations in each treatment and were repeated 3 times, thus there will be 36 experimental units. The parameters measured in the study were TBA, water activity, pH, total bacteria (TPC). Data analysis used Anova, if the impact is very significant (P<0.01) Duncan further test was conducted to determine the difference between treatment with SPSS 23 software. This study showed that the interaction between dragon fruit skin extract and the duration factor of watering had a very significant effect (P<0.01) on TBA, pH, TPC, antioxidant activity. The best combination for TBA, pH, TPC, antioxidant activity of meat se'i at 80% for 18 hours. While the activity of se'i water caused the Aw value to increase from 0.84 to 0.96, the best combination for the value of water activity meat se'i at the level of 60% with a length of 12 hours.